The Effect of Accrual Quality, Underwriter Reputation, and Family Involvement on Corporate Bond Under-pricing - Irma Suryani Indra; Elvira Luthan; Amy Fontanella (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
This study aims to determine how the influence of Accrual Quality, Underwriter's Reputation and Family Involvement on the under-pricing of corporate bonds in the manufacturing and banking industries during 2017-2021. This research is a quantitative study using secondary data collected through the IDX's official website and the company's website. The population used in this study were all manufacturing and banking companies that issued bonds in 2017-2021 using purposive sampling technique for the sample selection method. This study uses multiple linear analyses, which in this study shows that the reputation of the underwriter has a significant effect on the under-pricing of corporate bonds. Meanwhile, the quality of accruals and family involvement has no significant effect on the under-pricing of corporate bonds.